2019
DOI: 10.3390/cancers11010104
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Extracellular Vesicle-Associated-RNAs Induces Drug Resistance in ALK-Translocated Lung Adenocarcinoma

Abstract: Anaplastic lymphoma kinase (ALK) translocation is an actionable mutation in lung adenocarcinoma. Nonetheless tumour consists of heterogeneous cell subpopulations with diverse phenotypes and genotypes, and cancer cells can actively release extracellular vesicles (EVs) to modulate the phenotype of other cells in the tumour microenvironment. We hypothesized that EVs derived from a drug-resistant subpopulation of cells could induce drug resistance in recipient cells. We have established ALK-translocated lung adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Exosomes containing miR-222-3p are transferred to other cancer cells, where miR-222-3p directly regulates SOCS3 and develops malignant phenotypes of lung cancer cells along with gemcitabine resistance [183]. In addition, the therapeutic resistance to imatinib could be triggered by exosomal miR-365, which targets Bcl-2 associated X (BAX) in CML cells [184] (Figure 3 Consistent with the above observations, other studies found that exosomal miRNAs, miR-432a-5p, miR-486-3p, and miR-501-5p, could be derived from drug-resistant cancer cells, and these miRNAs develop the resistance in surrounding cells [185][186][187]. Exosomal miR-432a-5p transmits palbociclib resistance to other cancer cells via down-regulating SMAD4 and subsequently inducing CDK6 expression in breast cancer cells [185].…”
Section: Mir-222-3p and Mir-365supporting
confidence: 53%
See 1 more Smart Citation
“…Exosomes containing miR-222-3p are transferred to other cancer cells, where miR-222-3p directly regulates SOCS3 and develops malignant phenotypes of lung cancer cells along with gemcitabine resistance [183]. In addition, the therapeutic resistance to imatinib could be triggered by exosomal miR-365, which targets Bcl-2 associated X (BAX) in CML cells [184] (Figure 3 Consistent with the above observations, other studies found that exosomal miRNAs, miR-432a-5p, miR-486-3p, and miR-501-5p, could be derived from drug-resistant cancer cells, and these miRNAs develop the resistance in surrounding cells [185][186][187]. Exosomal miR-432a-5p transmits palbociclib resistance to other cancer cells via down-regulating SMAD4 and subsequently inducing CDK6 expression in breast cancer cells [185].…”
Section: Mir-222-3p and Mir-365supporting
confidence: 53%
“…In lung adenocarcinoma, one of the differentially expressed miRNAs in EVs released from drug-resistant cells is miR-486-3p. The delivery of miR-486-3p into surrounding cancer cells causes a down-regulation of PTEN and a development of resistance toward tyrosine kinase inhibitors [186]. Also, by targeting the BH3-like motif containing an inducer of cell death (BLID), exosomal miR-501-5p activates Akt signaling and represses caspase activation in recipient cells, eventually contributing to doxorubicin resistance in gastric cancer cells [187] (Figure 3).…”
Section: Mir-222-3p and Mir-365mentioning
confidence: 99%
“…In contrast to the previous section, studies also exist which describe the role of miRNA-486 in chemo-resistance. Extracellular vesicles (EVs) produced by ALK-translocated lung adenocarcinoma cell lines, which were rendered resistant to the ALK-TKIs crizotinib or ceretinib, were found to contain elevated levels of miRNA-486 amongst other non-coding RNAs [86]. When applied to drug-sensitive cell lines, the miRNA-486-containing EVs conferred resistance to both TKIs.…”
Section: Increased Mirna-486 Levels Promote Resistance To Treatment Imentioning
confidence: 99%
“…This combination, however, is not always successful. EVs from various origins operate in chemotherapy drug resistance by participating in various processes, such as expression of glutathione S-transferase or other enzymes; sequestration of cytotoxic drugs; capture of monoclonal antibodies by their binding to membrane proteins; and release to the cancer cell cytoplasm of specific proteins together with various coding and non-coding RNAs (see, among others, [ [72,73]]). These effects are at least potentially critical because, together with the cross-talk of cancer cells with stromal cells, they play substantial roles in the establishment of cancer.…”
Section: Diagnosis and Therapymentioning
confidence: 99%